Detrimental Effects of Diet-Induced Obesity on τ Pathology Are Independent of Insulin Resistance in τ Transgenic Mice - Leboucher, Antoine (American Diabetes Association, 2013)
The τ pathology found in Alzheimer disease (AD) is crucial in cognitive decline. Midlife development of obesity, a major risk factor of insulin resistance and type 2 diabetes, increases the risk of dementia and AD later in life. The impact of obesity on AD risk has been suggested to be related to central insulin resistance, secondary to peripheral insulin resistance. The effects of diet-induced obesity (DIO) on τ pathology remain unknown. In this study, we evaluated effects of a high-fat diet, given at an early pathological stage, in the THY-Tau22 transgenic mouse model of progressive AD-like τ pathology. We found that early and progressive obesity potentiated spatial learning deficits as well as hippocampal τ pathology at a later stage. Surprisingly, THY-Tau22 mice did not exhibit peripheral insulin resistance. Further, pathological worsening occurred while hippocampal insulin signaling was upregulated. Together, our data demonstrate that DIO worsens τ phosphorylation and learning abilities in τ transgenic mice independently from peripheral/central insulin resistance.